The association between constipation and subsequent risk of atopic dermatitis in children: the Japan Environment and Children's Study - Yoshihiko Takano; Yuri Aochi; Satoyo Ikehara; Kanami Tanigawa; Sachiko Baba; Keiichi Ozono; Tomotaka Sobue; Hiroyasu Iso (Komiyama Printing Co. Ltd, 2023)
Background: No study has examined the association between constipation and atopic dermatitis (AD) in infants and toddlers. We aimed to explore that association in toddlers using the data from a nationwide birth cohort study. Methods: From the Japan Environment and Children's Study, a nationwide prospective birth cohort study that began in 2011, children born in a singleton live birth were analyzed. Participants completed questionnaires containing questions related to bowel movements and AD, during 1.5 to 3 years after birth. Constipation at 1 year of age was defined as having ≤2 bowel movements per week. AD was defined based on participant's responses to the modified ISAAC questionnaire and/or self-reported physician's diagnosis. Outcome was defined as the cumulative number of AD cases that occurred until 3 years of age. Adjusted odds ratios (ORs) and 95% confidence intervals (CIs) for development of AD were calculated by a multivariable logistic regression. Results: From a total of 62,777 participants who met the study inclusion criteria, 14,188 children (22.6%) were affected by AD between the ages of 1.5 and 3 years. The adjusted OR of developing AD for the presence versus absence of constipation at 1 year of age was 1.18 (95% CI, 1.01-1.38). Conclusion: Constipation at 1 year of age was associated with a slightly higher risk of AD until 3 years of age.